2020
DOI: 10.1177/0194599820913495
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Heterogeneity in Otolaryngology Medicare New Patient Visits

Abstract: Objective To analyze the spatial variation of sociodemographic factors associated with the geographic distribution of new patient visits to otolaryngologists. Study Design Retrospective cross-sectional analysis. Setting United States. Subject and Methods Medicare new patient visits pooled from 2012 to 2016 to otolaryngology providers were obtained from the Centers for Medicare and Medicaid Services, and county-level sociodemographic data were obtained from the 2012-2016 American Community Survey. The mean numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The percentage of total visits in metropolitan versus nonmetropolitan areas, respectively, was reported by 55.8% and 90.2% in primary care, 19.3% and 5.2% in otolaryngology, and 18.4% and 1.6% in allergy/pulmonology. This reflects a relative scarcity of subspecialists in nonmetropolitan areas and contributes to the differences seen in patient presentation for those settings 3,5 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The percentage of total visits in metropolitan versus nonmetropolitan areas, respectively, was reported by 55.8% and 90.2% in primary care, 19.3% and 5.2% in otolaryngology, and 18.4% and 1.6% in allergy/pulmonology. This reflects a relative scarcity of subspecialists in nonmetropolitan areas and contributes to the differences seen in patient presentation for those settings 3,5 …”
Section: Discussionmentioning
confidence: 99%
“…This reflects a relative scarcity of subspecialists in nonmetropolitan areas and contributes to the differences seen in patient presentation for those settings. 3,5 The only R-RFVs that were seen most frequently by otolaryngologists were epistaxis and inflammation/swelling of the nose. 7,8 This suggests appropriate selection of specialty care, as studies have shown that otolaryngologists perform the most epistaxis-related interventions in the Medicare population nationally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations